Plasmodium falciparum aminopeptidases and their role in haemoglobin degradation in malaria-infected erthrocytes - Gavigan, Clare Sarah (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2001)
Malaria remains one of the world's most important infectious diseases. There is no vaccine available, and the spread of drug resistance has narrowed the choice of chemotherapy, especially for the most lethal human malaria parasite Plasmodium falciparum.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin